(untitled) (Itinera, 2018)
Passion, structure, and technique: these are the ‘colors’ that Diderot uses to ‘paint’ his opinions in his Salons. Greuze is staged passion, Vernet is form, rhythm and ideal, and while Chardin possesses the technique and touch that are able to say everything, François Boucher is the sterility of the gesture. In Diderot’s thought, virtue can also be seen in relation to the struggle against mediocrity and bad taste. In a society dominated by the petit goût and the sterile virtuosity of the petits maîtres, real genius suffocates as taste becomes perverted. In 18th-century society, there is no art without taste.